Optimization of hematoxylin and eosin staining of heart, blood vessels, liver, and spleen - L. A. Bogdanov; A. G. Kutikhin (Фундаментальная и клиническая медицина, 2019)
Aim. To optimize hematoxylin and eosin staining protocol for heart, blood vessels, liver, and spleen.Methods. Heart (ventricles), abdominal aorta, liver (right lobe), and spleen (left part) of the Wistar rats were excised, fixed in 10% neutral phosphate buffered formalin for 24 h, washed in tap water for 2 h, dehydrated in ascending ethanol series (70%, 80%, and 95%) and isopropanol, embedded into paraffin and then sectioned (5 μm) using rotary microtome. For regressive staining, incubation time in Harris hematoxylin was 5 or 10 minutes, time of exposure to differentiation alcoholicaqueous eosin was 1 or 2 minutes. For progressive staining, incubation time in Carazzi’s hematoxylin and eosin was the same but the differentiation solution was not utilized.Results. Progressive staining retained tissue integrity and accelerated staining protocol as compared to regressive staining due to absence of exposure to aggressive acid alcohol differentiation solution. The optimized protocol for heart, aorta and liver, similar for regressive and progressive staining, included incubation in hematoxylin for 10 minutes and eosin for 2 minutes. Time of exposure to differentiation solution (2 or 10 seconds) was defined by the desirable shade. For spleen, however, the optimized protocol included staining in hematoxylin for 5 minutes and eosin for 2 minutes, with 10 seconds in differentiation solution for regressive staining.Conclusion. Progressive hematoxylin is preferable over regressive hematoxylin for staining of heart, aorta, liver, and spleen.